2010
DOI: 10.1039/c0cp00055h
|View full text |Cite
|
Sign up to set email alerts
|

Infra-red and Raman spectroscopy of free-base and zinc phthalocyanines isolated in matrices

Abstract: The infrared absorption spectra of matrix-isolated zinc phthalocyanine (ZnPc) and free-base phthalocyanine (H 2 Pc) have been recorded in the region from 400 to 4000 cm À1 in solid N 2 , Ar, Kr and Xe. Raman spectra have been recorded in doped KBr pellets. The isotopomers HDPc and D 2 Pc have been synthesised in an attempt to resolve the conflicting assignments that currently exist in the literature for the N-H bending modes in H 2 Pc spectra. A complete correlation between the vibrational modes of the three f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 28 publications
10
55
0
Order By: Relevance
“…It is worth mentioning that the recent X-ray studies [26] on three axial ZnPc•••n-alkylamines nicely agree with our data and prove the existence of similar nonplanar structures with d parameter of about 0.5 Å. In addition, the subsequent B3LYP/6-31+G(d) [70] b HF, B3LYP, and MP2 with 6-31G* result from [41] c UB3LYP/6-31G(d,p) data for ZnPc, from [71] d B3LYP/6-31G** data from [34] e B3LYP/6-31G* data for ZnPc, from [72] f X-ray data for ZnPc, from [20] g ED data from [21] h Reinvestigation of ED data from [22] i ED data for SnPc, from [22] j ED data for MgPc, from [22] k Laser-desorption supersonic jet spectroscopy data for H2Pc with D 2h symmetry; planar are also MgPc and ZnPc with D 4h symmetry, from [27] l ED data from [35] [75] e X-ray data for ZnPc•••n-hexylamine, from [24] calculations by these authors [26] closely reproduced the observed crystal structure of these solvates (d was about 0.43 Å …”
Section: Structural Feature Of the Znpc···h 2 O Complexsupporting
confidence: 88%
“…It is worth mentioning that the recent X-ray studies [26] on three axial ZnPc•••n-alkylamines nicely agree with our data and prove the existence of similar nonplanar structures with d parameter of about 0.5 Å. In addition, the subsequent B3LYP/6-31+G(d) [70] b HF, B3LYP, and MP2 with 6-31G* result from [41] c UB3LYP/6-31G(d,p) data for ZnPc, from [71] d B3LYP/6-31G** data from [34] e B3LYP/6-31G* data for ZnPc, from [72] f X-ray data for ZnPc, from [20] g ED data from [21] h Reinvestigation of ED data from [22] i ED data for SnPc, from [22] j ED data for MgPc, from [22] k Laser-desorption supersonic jet spectroscopy data for H2Pc with D 2h symmetry; planar are also MgPc and ZnPc with D 4h symmetry, from [27] l ED data from [35] [75] e X-ray data for ZnPc•••n-hexylamine, from [24] calculations by these authors [26] closely reproduced the observed crystal structure of these solvates (d was about 0.43 Å …”
Section: Structural Feature Of the Znpc···h 2 O Complexsupporting
confidence: 88%
“…This is currently the most effective theoretical method for obtaining ground state molecular vibrational frequencies. Moreover, as established in our previous study 27 of zinc and free base phthalocyanine, the Raman intensities are also reliable. A variety of basis sets were utilised during the course of this work -specifically the 6-31g(d), 6-311G++(2d,2p), and 6-311G++(3df,3pd) -but only the results of the largest one are utilised in this work.…”
Section: B Theoreticalsupporting
confidence: 64%
“…9 However, as will be shown later, the upward shifts in the heavier isotope were much larger than what we have seen with the force fields generated in the present quantum chemical method. The earlier work 8 only considered in-plane vibrations, i.e., the N-H stretches and in-plane bending modes, but as we have found experimentally 6 , the most easily identifiable instance of the reversed ISR effect in the phthalocyanines involved an out-of-plane N-H bending motion. A more recent DFT calculation of free-base phthalocyanine by Liu et al also found a reverse ISR.…”
Section: Introductionmentioning
confidence: 58%
“…Moreover, for the free-base tetrapyrroles, H/D substitution of the two inner hydrogens is particularly appealing as the D 2h molecular symmetry is conserved, allowing direct comparisons between the two isotopologues. However, in a recent combined IR/Raman and high-level density functional theory (DFT) study 6 of free-base phthalocyanine (H 2 Pc), we observed quite peculiar behaviour upon H/D substitution, whereby the frequency of one particular mode of the deuterium isotopologue was found to be higher than that of hydrogen. The mode in question is the IR-active out-of-plane bending vibration observed in Ar matrices at 722.7 cm -1 for H 2 Pc, but which shifts up to 729.9 cm -1 in D 2 Pc.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation